(untitled) (Research, Society and Development, 2020)
Constantly in Brazil and around the world, there are several changes of economic and financial nature. As society expands and new financial needs evolve. Given this fact and with the advancement of information technology in the world, credit cooperatives have emerged as tools for economic development, with financial offers, and services with more attractive rates and greater participation of society. This research aims to portray about the financial statements that the Nova Serrana cooperative discloses in its channel and the influence they have on the appointment and loyalty of members. According to bibliographic research the history of cooperativism is rescued, demonstrating how the first credit unions emerged and how important they are today. It highlights the characteristics of credit unions and their differences with other financial institutions, a brief explanation of the financial statements. , relational marketing with the capture and loyalty of members, and finally to answer the problem and achieve the research objective is made an analysis of the perception of the influence of the statements to the member before the cooperative in which he participates. The research is conducted in a credit union of Nova Serrana-MG, through the application of questionnaires that were answered by a sample of members of the cooperative studied, seeking to identify what are the main factors that would lead the indication of the credit union. As a result, we note that the members consider the financial statements important, but demonstrate that for them there are other factors considered more relevant to the loyalty of members.